A Case Study: Revealing The Result And Challenges Of Accommodating Authentic Materials And Schoology For Teaching Writing In EFL Context - Dewi Cahyaningrum (Jurnal Dimensi Pendidikan dan Pembelajaran, 2021)
Learning writing in EFL context, students have limited opportunities to write in English both inside and outside of the class since they have less immediate English needs. In this situation, they require abundant exposure to written language over time. To help the students to write better, in this research, teacher accommodates Authentic Materials and Schoology in order to support the students in mastering writing skill. Reviewing many references, the writer found the effectiveness of authentic materials for teaching writing. Similarly, Tomlinson (2012) underlined the characteristics of ideal materials for English Language Teaching (ELT) that is having authentic input features. These authentic materials help the students to acquire the language effectively. In 4.0 era, Schoology is one of educational websites that can be applied by teacher and students for collaborating about resources, learning content-activities, and assessment on a secure and safe learning management platform. Students can post their writing task in Schoology in the form of online portfolios while the teacher can evaluate the students’ writing and give some suggestion or comments. Schoology also provides possibility for teacher to provide scoring rubrics to help students in generating texts. In general, this paper is a case study result paper discussing about (1) the idea of accommodating Authentic Materials and Schoology in order to support the students in mastering writing skill, and (2) challenges for the teacher to accommodate Schoology in writing class, and (3) challenges for the teacher to use Authentic Materials for teaching writing.